Efisiensi Panel Surya Kapasitas 100 Wp Akibat Pengaruh Suhu Dan Kecepatan Angin - Dahliya Dahliya; Samsurizal Samsurizal; Nurmiati Pasra (Sekolah Tinggi Teknik - PLN, 2021)
Solar radiation has a great effect on the output of the photovoltaic system. Wind speed is directly related to the cooling of the PV system and can also affect the performance of the solar collector. This research looks at the influence of temperature and wind on the efficiency of solar panels. From the results of the tests and calculations, it was found that the temperature of the single crystal panel measured on that day was 44°C, and the temperature of the polycrystalline panel was 43°C. The effect of wind speed on the efficiency of the solar module, calculated based on calculations using the linear regression method, shows a correlation level of R = 0.0281. This means that only about 2.81% wind speed will affect it. Has solar module efficiency. From the various aspects of the calculations carried out, we can see that the efficiency of the single crystal panel is 11.716%, while the efficiency of the polycrystalline panel is 10.02%. From the calculation results, we can conclude that the efficiency of the single crystal module is significantly increased.